1997
DOI: 10.1097/00006123-199712000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Basilar Aneurysm after Endoscopic Third Ventriculostomy: Case Report

Abstract: Hemorrhagic complications after endoscopic third ventriculostomy are rare. The formation of a traumatic basilar tip aneurysm after this procedure has not been reported in the literature. Laser fenestration of the third ventricular floor may increase the risk of this event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
95
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(97 citation statements)
references
References 18 publications
1
95
0
1
Order By: Relevance
“…Others have raised concern regarding the high mortality (as reviewed by Hoffman et al [17]at 0–20% for percutaneous TV) and morbidity (e.g. cardiac arrest, vascular perforation, diabetes insipidus, syndrome of inappropriate antidiuretic hormone secretion, subdural hematoma or meningitis) [8, 18, 19, 20, 21]associated with the procedure – sequela which are essentially nonexistent secondary to a CS procedure. Reports of unsuccessful completion of the procedure due to technical difficulties are as high as 26% [3].…”
Section: Discussionmentioning
confidence: 99%
“…Others have raised concern regarding the high mortality (as reviewed by Hoffman et al [17]at 0–20% for percutaneous TV) and morbidity (e.g. cardiac arrest, vascular perforation, diabetes insipidus, syndrome of inappropriate antidiuretic hormone secretion, subdural hematoma or meningitis) [8, 18, 19, 20, 21]associated with the procedure – sequela which are essentially nonexistent secondary to a CS procedure. Reports of unsuccessful completion of the procedure due to technical difficulties are as high as 26% [3].…”
Section: Discussionmentioning
confidence: 99%
“…With the distortion of the third ventricular floor, the risk of injury to the vulnerable basilar artery complex increases. Basilar artery complex perforation is a devastating complication which may result in subarachnoid hemorrhage, intraventricular hemorrhage, traumatic aneurysm formation, or death [4, 7, 8, 9, 10, 11, 12]. Management of a basilar artery complex perforation consists of copious intraventricular irrigation, carefully ensuring to not overinflate the ventricular system.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic angiography should then be performed in order to identify damage to the basilar artery complex. McLaughlin et al [11]reported the delayed formation of a traumatic basilar apex aneurysm after an intial negative angiogram; therefore, four-vessel angiography should be postponed several days to allow formation of the potential pseudoaneurysm. Traumatic aneurysm formation requires direct repair via an appropriate craniotomy [4, 7, 11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm that ETV is a successful and safe procedure for the treatment of occlusive hydrocephalus. Other authors observed that serious morbidity and mortality associated with ETV during perforation of the third ventricular floor due to damage of the basilar artery or another vessel of the distal basilar artery complex (BA complex) may occur [17, 18, 19, 20]. …”
Section: Introductionmentioning
confidence: 99%